Lost in Translation: Shop Signs in Jordan - Al-Kharabsheh, Aladdin; Al-Azzam, Bakri; Obeidat, Marwan (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractShop signs, in the Jordanian public commercial environment, have invariably been studied from linguistic, sociolinguistic, and pragmatic perspectives, but they have been utterly ignored from a translational point of view. This study, the first of its kind, investigates various problems and inadequacies pertinent to the subject under discussion. Shop signs are selected here from a number of heterogeneous cities, and the translation errors therein, committed by communicators, were empirically analyzed and categorized. Language and culture are, of necessity, inextricably intertwined, and this nexus is particularly apparent in the world of local commercial shop signs, and thus it has been tackled for its direct relevance to the translation of these signs. This investigation, therefore, highlights the linguistic (e.g., word-order, wrong lexical choice, and reductionist strategies), and extralinguistic (i.e., sociocultural and promotional) factors that have turned out to lead to translation inappropriateness and unparallelisms, information skewing, and, consequently, serious semantic-conceptual problems in the produced TLTs. This study may, in a way, provide educated insight into the trendiest translation practices in this field, and the way shop signs are most often verbalized, mishandled, and mistranslated.